A CASE STUDY ON MANDARIN TEXT-TO-SPEECH - Yoke Lian Lau; Wan Hurani Osman; Bernadette Tobi; Irma Wani Othman, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
There are three objectives of this study. First, to investigate the effectiveness of TTS in Mandarin language reading, find out the shortage of TTS, and understand the difference between machine-reading and human reading. Second, the study concludes that TTS technology is mature enough now but still needs to solve some problems in specific criteria such as conveying humanity elements, putting in more human nature, and expressing human emotions in the reading process in the future. Third, teaching mandarin reading is still necessary as the TTS system could not, instead of the importance of a teacher in reading and learning thoroughly.